Diversidad Genetica de Oreopanax xalapensis (Araliaceae) en los Altos de Chiapas - Ruiz-Montoya, L.=700 1 Correa-Vera, V.; Alfaro-Gonzalez, F.C.; Ramirez-Marcial, N.; Veronica-Vallejo, R.
(En, Es)
Ilus., 75 ref
Keywords: ARALIACEAE; VARIACION GENETICA; REHABILITACION FORESTAL; CHIAPAS; MEXICO; OREOPANAX XALAPENSIS; BOLETIN DE LA SOCIEDAD BOTANICA DE MEXICO